2010
DOI: 10.4103/0378-6323.58672
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of low-dose isotretinoin in acne vulgaris

Abstract: Low-dose isotretinoin (0.5 mg/kg/day) is a mode of therapy for mild to moderate grades of acne. We analyzed the various trials of this mode of therapy with or without combination with topical agents. We also statistically analyzed the results, efficacy and relapse rates of standard therapy in comparison with the low-dose therapy. Our analysis of the data revealed that the efficacy and relapse rates of low-dose isotretinoin in mild to moderate grades of acne is comparable with the standard regimen (1 mg/kg/day)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 28 publications
1
35
0
1
Order By: Relevance
“…These regimens vary from daily therapy to intermittent or alternate day therapy, with an overall dose of 0.14-0.75 mg/kg/day (11). Using an isotretinoin-sparing protocol which sought to reduce total cumulative dose, Borghi et al recently reported a remission rate of more than 90% at a low mean cumulative dose of 80.9 mg/kg (12).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…These regimens vary from daily therapy to intermittent or alternate day therapy, with an overall dose of 0.14-0.75 mg/kg/day (11). Using an isotretinoin-sparing protocol which sought to reduce total cumulative dose, Borghi et al recently reported a remission rate of more than 90% at a low mean cumulative dose of 80.9 mg/kg (12).…”
Section: Introductionmentioning
confidence: 98%
“…Recently, there has been a shift to the use of lower and more intermittent dosage regimens to decrease dose-related side-effects (10,11). These regimens vary from daily therapy to intermittent or alternate day therapy, with an overall dose of 0.14-0.75 mg/kg/day (11).…”
Section: Introductionmentioning
confidence: 99%
“…[43,44] Isotretinoin 20 mg in an alternate day regimen seems to be an effective and safe treatment option in mild to moderate cases, according to an Indian study. [45] However, intermittent regimens with 0.5-0.7 mg/kg/day of isotretinoin for a week, every 4 weeks, did not achieve good patient satisfaction and remission.…”
Section: Synergistic Topical Combinationsmentioning
confidence: 95%
“…Finasteride doses as low as 0.2 mg/day adequately suppress both scalp skin and serum dihydrotestosterone levels, with clinical efficacy comparable to higher daily doses of 1 and 5 mg. [54] Similarly, low dose isotretinoin has been reported to be equi-efficacious to higher doses in multiple acne trials. [55] To vitiate the possibility of nocebo effect, isotretinoin may be initially administered at a lower daily dose (0.3 mg/kg) or on alternate days, followed by the full therapeutic dose (0.5-1 mg/kg/day), once the patient is comfortable. The value of similar regimens has been proven in a preliminary study.…”
Section: Management Strategies To Alleviate Nocebo Effect In Clinicalmentioning
confidence: 99%